MANAJEMEN PENGEMBANGAN PONDOK PESANTREN (Studi Kasus di Pondok Pesantren As’adiyah Belawa Baru, Masamba, Sulawesi Selatan) - Yunus, Yunus; Mukhtar, Jazuli; Nugroho, Ichwan (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
This study aims to determine the pattern of development strategy Boarding School in Malangke. Pattern or strategic used by the container or place in order to process a change of plans that require the support of all parties to develop and improve educational quality. In this study, researchers used a qualitative research and data sources through interviews with the leadership of the cottage. Boarding school development opportunities in the North Luwu, belonging to the sub-national education system in Indonesia that aims to educate the nation, making the man who is faithful and devoted to God Almighty, noble, healthy, knowledgeable, skilled, creative. In addition, the boarding school New Belawa As'adiyah, considered successful because students-students directly involved in the community, for example in the Holy month of Ramadhan, these students were sent to be Imam in every mosque in Malangke. But beyond the success, there are some some of the barriers faced by Islamic Schools As'adiyah New Belawa (Malangke) include: 1) a more modern curriculum system, so that schools lag far from public schools, 2) Lack of funds and sources of funding due to lack of students. 3) the majority of parents are not keen to send children in school boarding school.